Efektivitas Penggunaan ITN (Insecticide Treated Nets) terhadap Penurunan Kasus Malaria pada Anak di Bawah 5 Tahun di Indonesia - Khairunnisa, Dhiennada Putri; Katon, Hilda Sri; Andriani, Helen; Permanasari, Vetty Yulianty (Pustaka Kesehatan, 2025)
Malaria is caused by the Plasmodium parasite and is transmitted through the bites of infected Anopheles mosquitoes, which are prevalent in tropical regions, including Indonesia. In 2010, Indonesia recorded 465.7 thousand positive malaria cases, but this number decreased to 235.7 thousand in 2020. Additionally, the Annual Parasite Incidence (API) also showed a decline from 1.96 in 2010 to 0.87 in 2020. Various preventive measures have been implemented, including the use of Insecticide-Treated Nets (ITN). This research employed a literature review method with the PRISMA (Preferred Reporting Items for Systematic Review & Meta-Analysis) approach, gathering data from international journal sources such as Google Scholar and PubMed, comprising a total of 13 journal articles. The study found that ITNs can reduce the incidence of malaria, particularly among children under five years old in Indonesia. The government's program for distributing ITNs has proven effective in decreasing malaria cases. Health workers, community health volunteers, and community-based health service centers play a crucial role in disseminating information, distributing, and promoting the use of ITNs. Based on the literature review, it was concluded that the use of ITNs is effective in reducing malaria cases in children under 5 years old in Indonesia.